The power to control the media in Algeria between independence and dependency - Benmeggoura, Djenette (Journal of Human Sciences, 2021)
The media sector is one of the important and sensitive sectors, to the point that it recognizes as the authority, but the Egyptian constitution devoted it in a chapter under the name of "the fourth authority". Algeria has attached great importance to this sector, through the creation of new institutions that will take over the management of the sector without any monopoly of the state. In spite of the explicit recognition of the independence of these authorities, through the recognition of aspects of organic and functional independence, this independence sometimes collides with the presence of restrictions that make them relative independence.